2007
DOI: 10.1021/ef0701440
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Catalyzed Transesterification of Canola Oil to Biodiesel under Single- and Two-Phase Reaction Conditions

Abstract: Experiments were performed at ambient temperature to investigate the effects of mass transfer during the transesterification reaction of canola oil with methanol (MeOH) to form fatty acid methyl esters using a sulfuric acid (H2SO4) catalyst at a MeOH/oil molar ratio of 6:1. Experiments at ambient conditions resulted in reaction rates that were slow enough to permit the effects of mass transfer on the transesterification reaction to become more evident than at higher temperatures. For the two-phase experiments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
76
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 32 publications
2
76
2
Order By: Relevance
“…Lower mass transfer coefficients were reported for lower temperatures, since the mass transfer coefficients obtained by Frascari et al (2009) at 60 °C were greater than that obtained by Klofutar et al (2010) at 40 °C and 50 °C. The mass transfer coefficient (k c a) determined by Ataya et al (2007) was much lower than that reported in the other literature. In the case of Liu et al (2010), the apparent mass transfer coefficient value is not representative of the maximal coefficient that can be reached by reacting molecules before the reaction will occur, since the determination of mass transfer parameters was performed without acknowledging the experimental regime and the coefficient was consequentially unusually high.…”
contrasting
confidence: 66%
See 2 more Smart Citations
“…Lower mass transfer coefficients were reported for lower temperatures, since the mass transfer coefficients obtained by Frascari et al (2009) at 60 °C were greater than that obtained by Klofutar et al (2010) at 40 °C and 50 °C. The mass transfer coefficient (k c a) determined by Ataya et al (2007) was much lower than that reported in the other literature. In the case of Liu et al (2010), the apparent mass transfer coefficient value is not representative of the maximal coefficient that can be reached by reacting molecules before the reaction will occur, since the determination of mass transfer parameters was performed without acknowledging the experimental regime and the coefficient was consequentially unusually high.…”
contrasting
confidence: 66%
“…Experiments were also performed by Ataya et al (2007) at ambient temperature to investigate the effects of mass transfer during the transesterification reaction of canola oil with methanol (CH 3 OH) to form fatty acid methyl esters using a sulfuric acid (H 2 SO 4 ) catalyst at a CH 3 OH/oil molar ratio of 6:1. Experiments at ambient conditions result in reaction rates that are slow enough to permit the effects of mass transfer on the transesterification reaction to become more evident than at higher temperatures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two types of transesterification have been developed and analysed for biodiesel production using either chemical catalyst or biological catalyst [4][5][6][7]. There are ample research articles where alkaline transesterification for biodiesel production is investigated [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This property is justified by the fact of canola oil being rich in unsaturated fatty acids, Table 1. This oil has been used in several studies to test transesterification reactions conducted under adverse conditions, such as heterogeneous catalysts [19][20][21], in situ reactions [22], use of ultrasound [23] and alcohol in supercritical state [24], etc. In most studies, the type of alcohol employed was the methanol.…”
Section: Introductionmentioning
confidence: 99%